Ethical Process in Decision-Making for A Synodal Church - Jipson Joseph Edappulavan (Asian Horizons, 2025)
Decision-making is the most essential nature of a person as a rational being. Being a member of a family or a society or an institution, his or her decision-making power influences others also in a myriad of ways. Generally, the decision of a powerful and authoritarian person becomes the decision of the group or that of an institution. The Church, too, at certain times, has become institutionalised in its decision-making process. The age-old hierarchical nature of the Church underlines the importance of the synods in its decision-making processes. But at the same time, the synodal model tries to establish a new ethical model of decision-making, which insists on the walking together of the entire people of God without any discrimination in arriving at proper and meaningful decisions. It uplifts the lay faithful as essential elements of decision-making and Pope Francis urges the bishops to consult their priests and the lay faithful in order to arrive at good decisions. Open, free, and honest discussions, patiently listening to one another, and consensus-building are the different stages of this new synodal model of decision-making. It also affirms that decision-making should be characterised by discernment, participatory-consultation, and co-responsibility.